The structural gene for a phosphorus-repressible phosphate permease in Neurospora crassa can complement a mutation in positive regulatory gene nuc-1. - Mann, B J (1988)
van+, a gene encoding a phosphorus-repressible phosphate permease, was isolated by its ability to complement nuc-1, a positive regulatory locus that normally regulates van+ expression. This was unexpected because the nuc-1 host already contained a resident van+ gene. Plasmids carrying van+ complemented a nuc-2 mutation as well. Probing of RNA from untransformed wild-type (nuc-1+) and constitutive (nuc-1c) strains by van+ probes indicated that levels of the van+ transcript were subject to control by nuc-1+. Probing of the same RNAs with a cosmid clone, containing approximately 15 kilobases of upstream and downstream DNA, revealed no other detectable phosphorus-regulated transcripts within this 40-kilobase region of the chromosome.